2016
DOI: 10.1002/jmv.24546
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal analysis of the humoral response to Kaposi's sarcoma-associated herpesvirus after primary infection in children

Abstract: Kaposi's sarcoma-associated herpesvirus (KSHV) is the etiologic agent for Kaposi's sarcoma (KS)-one of the most common pediatric cancers in sub-Saharan Africa-however, the factors that lead to disease progression are not fully understood. HIV infection, immunosuppression, and high KSHV viral load increase the risk of developing KS, suggesting that the loss of an effective anti-KSHV immune response may be an important risk factor. However, very little is known about the KSHV-specific immune response prior to KS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 28 publications
(40 reference statements)
1
7
0
Order By: Relevance
“…In this study, all animals were regularly monitored for clinical signs and symptoms throughout the experiment period. They developed an intermittent and transient type of infection similar to phenomena reported in different populations ( Olp et al, 2016 ). Further, we used RT-PCR to detect mRNA levels in the peripheral blood samples.…”
Section: Discussionsupporting
confidence: 81%
“…In this study, all animals were regularly monitored for clinical signs and symptoms throughout the experiment period. They developed an intermittent and transient type of infection similar to phenomena reported in different populations ( Olp et al, 2016 ). Further, we used RT-PCR to detect mRNA levels in the peripheral blood samples.…”
Section: Discussionsupporting
confidence: 81%
“…Systemic analysis of antibodies to all KSHV proteins showed that ORF38, ORF61, ORF59 and K5 elicited detectable responses in individuals with KSHV-associated diseases 110 . However, antibodies to KSHV are rarely neutralizing 111 .…”
Section: Mechanisms/pathophysiologymentioning
confidence: 99%
“…Children in SSA, and elsewhere, are often exposed to infectious diseases at a young age, which makes infant vaccination crucial for effective disease control and child well-being and development. Indeed, our lab and others have demonstrated that seroconversion to Kaposi's Sarcoma Herpesvirus (KSHV) occurs in sub-Saharan infants at levels near the adult prevalence by 4 years of age [37,38]. Using adenoviruses as a vaccine vector has been shown to elicit strong T and B cell responses to inserted transgenes and could also confer immunity to the Ad used as the backbone, thereby decreasing the burden of adenovirus associated diseases in young children.…”
Section: Discussionmentioning
confidence: 99%